Implementation of Maqāṣid al-Sharī’ah Values in the Family Hope Program (PKH) as an Effort to Realize a Maslahah Family - Ahmad Zaenudin; Agus Setiawan; Habib Sulthon Asnawi; Ahmad Muslimin (Assyfa Journal of Islamic Studies, 2026)
This study aims to analyze the implementation of Maqāṣid al-Sharī’ah values in the Family Hope Program (PKH) as an effort to realize a maslahah family in Bandar Surabaya District, Central Lampung Regency. The research focuses on PKH implementation, reflected maqasid values, level of alignment, and implications for maslahah families. A qualitative case study approach was employed. Data were collected through in-depth interviews, participatory observation, and documentation involving the PKH District Team Leader, facilitators, beneficiary families (KPM), Social Service officers, and community leaders. Data analysis used the Miles & Huberman interactive model with validity ensured through source, technique, and time triangulation, member checking, audit trail, and reflexivity. The findings reveal: (1) PKH implementation has followed procedural mechanisms, yet variations exist in KPM understanding and participation; (2) Ḥifẓ al-nafs (protection of life) and ḥifẓ al-’aql (protection of intellect) are relatively stronger than ḥifẓ al-dīn (protection of religion), ḥifẓ al-nasl (protection of lineage), and ḥifẓ al-māl (protection of property); (3) The alignment of PKH implementation with Maqāṣid al-Sharī’ah is partial; (4) PKH contributes to basic needs fulfillment but has not fully fostered self-reliance or holistic maslahah families. This study recommends strengthening empowerment approaches and integrating religious values into social protection policies.